Discovering indigenous lands the doctrine of discovery in the English colonies - Behrendt, Larissa (Oxford : Oxford University Press, 2010)
North America, New Zealand and Australia were colonised by England under an international legal principle that is known today as the doctrine of discovery. This book analyses how this doctrine was used to gain control over the indigenous peoples, and how this control continues to this day.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Constitutional law -- Great Britain -- Colonies; Indigenous peoples -- Civil rights -- Great Britain -- Colonies; Great Britain -- Colonies -- Discovery and exploration